Hubungan Antara Kemampuan Memahami Kitab Kuning dengan Kemampuan Lisan dan Tulisan dalam Bahasa Arab - Tamam, Badrut (SYAMIL, 2015)
This research is intended to find out correlation of 1) how is ability to understanding yellow book student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School, 2) how is oral ability in arabic language student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School, 3) how is writing ability in arabic language student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School, 4) how is the relationship between the ability to understand the capability Yellow Book Oral and Written in Arabic student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School. This research belongs to quantitative correlation by taking Nahdlatul Wathan Tenggarong Seberang Islamic boarding school. Data was obtained by interview, observation, documentation and instrument. Data analysis techniques performed with the test requirements analysis to test the research hypothesis. Finding of this research show that ability to understanding yellow book student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School year academic 2015-2016 show that in general ability of understanding yellow book student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School have ability to fairly high significance with an average mean 71.98 and standart deviation of 9.743. The ability of verbal have average score mean is 76.03. Shows the direction quite high with standard deviations is 10 407. The ability of writinghave average score mean is 76.77. Shows the direction quite high with standard deviations is 80.Partially multiple correlation the ability to understand the capability Yellow Book Oral and Written in Arabic student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School showing the conclution: 1) The absence of a significant positive relationship between the ability to understand the yellow book with verbal ability is shown by a coefficient of 0.124. 2) While the ability to understand the yellow book with writing ability enough to have a significant relationship with a coefficient of 0.009. 3) There is a positive relationship between the yellow book with the ability to understand spoken and written ability student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School. The strength of correlation the ability to understand the capability Yellow Book, Oral and Written in Arabic student of Nahdlatul Wathan Tenggarong Seberang Islamic Boarding School indicated by the multiple correlation coefficient of 0.503.